2013
DOI: 10.5966/sctm.2012-0181
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Tissue-Engineered Skin and Nerve Regeneration in Burn Treatment

Abstract: Burns not only destroy the barrier function of the skin but also alter the perceptions of pain, temperature, and touch. Different strategies have been developed over the years to cover deep and extensive burns with the ultimate goal of regenerating the barrier function of the epidermis while recovering an acceptable aesthetic aspect. However, patients often complain about a loss of skin sensation and even cutaneous chronic pain. Cutaneous nerve regeneration can occur from the nerve endings of the wound bed, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 67 publications
(68 reference statements)
0
79
0
1
Order By: Relevance
“…Four weeks after thermal injury, nerve trunks run perpendicularly to the surface of the scar with a "characteristically varicose appearance", and at 4 months after burn there was no significant difference in axon counts between burned and control skin, though in some cases there may have been an increase in the density of axons in the burned skin (Ward et al, 1998). No studies conducted thus far have determined whether the axonal ingrowth is from regenerating axons that had been injured by the burn or from intact axons innervating neighboring skin which reinnervated the recovered skin by collateral sprouting (Blais et al, 2013;Diamond et al, 1987;Diamond et al, 1992aDiamond et al, , 1992bGloster and Diamond, 1992), though it is most likely both. This concept is schematized in Fig.…”
mentioning
confidence: 84%
“…Four weeks after thermal injury, nerve trunks run perpendicularly to the surface of the scar with a "characteristically varicose appearance", and at 4 months after burn there was no significant difference in axon counts between burned and control skin, though in some cases there may have been an increase in the density of axons in the burned skin (Ward et al, 1998). No studies conducted thus far have determined whether the axonal ingrowth is from regenerating axons that had been injured by the burn or from intact axons innervating neighboring skin which reinnervated the recovered skin by collateral sprouting (Blais et al, 2013;Diamond et al, 1987;Diamond et al, 1992aDiamond et al, , 1992bGloster and Diamond, 1992), though it is most likely both. This concept is schematized in Fig.…”
mentioning
confidence: 84%
“…As collagen is degraded, neovascularization and granulation tissue supports the transplanted minced particles that reorganize, migrate and expand [5][6][7]11,16 . Besides, collagen is a major natural component of the extracellular matrix both in skin and in the bladder and has been used for creation of scaffolds both in vitro and in vivo including wound healing studies and reconstructions in the urogenital system 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…44 This nerve regeneration process is imperfect. It was reported that 71% of extensively burned victims suffer from abnormal sensation and 36% from chronic pain.…”
Section: Neurologicalmentioning
confidence: 99%